2011
DOI: 10.1080/14783363.2010.532319
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of cultural adaptation, communication quality, and trust in virtual teams' performance

Abstract: A virtual team is a network group where team members from different cultures are temporarily gathered together for the period of a mission. The present research proposes a general model of virtual teams to investigate how cultural adaptation, communication quality, and trust affect the performance of virtual teams and their interaction with each other. A qualitative method is applied in the study. Four virtual team members from diverse teams are interviewed in order to explore how virtual teams work and whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 50 publications
1
19
0
1
Order By: Relevance
“…Our findings are in line with Chang, Chuang, and Chao's proposition, in which they suggested that individual's cultural adaptation was positively related to communication quality and trust [10]. Our study confirmed this effect by assessing cultural adaptation with cultural intelligence and testing causal relationships using an experiment setting analyzed within the PLS structural equation framework.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are in line with Chang, Chuang, and Chao's proposition, in which they suggested that individual's cultural adaptation was positively related to communication quality and trust [10]. Our study confirmed this effect by assessing cultural adaptation with cultural intelligence and testing causal relationships using an experiment setting analyzed within the PLS structural equation framework.…”
Section: Discussionsupporting
confidence: 91%
“…It is defined as positive expectation, attitude, belief or confidence about the other party's behaviour even if the risk of being hurt exists (Piniani & Palvia, 2013;Castaldo at al., 2010, p. 658]. Trust is the will to rely or depend on other people -their intentions, motives and behaviours (Chang at al., 2011;Smyth at al., 2010, p. 119). Trust is also strictly connected to interdependence, which is a basic feature of teamwork (DeOrtentiis at al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We have not been able to systematically measure the long‐term impacts of the organisational culture handbook on, for example, firm performance or organisational trust. Further research could investigate the impact of substitutes for socialisation in virtual organisations, drawing on the relevant literature (eg, Chang, Chuang, & Chao, 2011; Choi & Cho, 2019; Martinez, Beaulieu, Gibbons, Pronovost, & Wang, 2015; Ogbonna & Harris, 2000; Scheibe & Gupta, 2017).…”
Section: Discussionmentioning
confidence: 99%